2012
DOI: 10.1186/1471-2229-12-34
|View full text |Cite
|
Sign up to set email alerts
|

Betalain production is possible in anthocyanin-producing plant species given the presence of DOPA-dioxygenase and L-DOPA

Abstract: BackgroundCarotenoids and anthocyanins are the predominant non-chlorophyll pigments in plants. However, certain families within the order Caryophyllales produce another class of pigments, the betalains, instead of anthocyanins. The occurrence of betalains and anthocyanins is mutually exclusive. Betalains are divided into two classes, the betaxanthins and betacyanins, which produce yellow to orange or violet colours, respectively. In this article we show betalain production in species that normally produce anth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 28 publications
2
82
0
2
Order By: Relevance
“…These findings indicated that there is DO activity of tyrosinase (TYR) present in some of the anthocyanin producing plants. It could be also possible that the L-DOPA to dopaquinone oxidation was carried out by a cytochrome P450 encoded by CYP76AD1 (Hatlestad et al, 2012). In another recent study, betalain biosynthesis was achieved in non-betalain accumulating plants viz.…”
Section: Mutual Exclusiveness Of Anthocyanins and Betalainsmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings indicated that there is DO activity of tyrosinase (TYR) present in some of the anthocyanin producing plants. It could be also possible that the L-DOPA to dopaquinone oxidation was carried out by a cytochrome P450 encoded by CYP76AD1 (Hatlestad et al, 2012). In another recent study, betalain biosynthesis was achieved in non-betalain accumulating plants viz.…”
Section: Mutual Exclusiveness Of Anthocyanins and Betalainsmentioning
confidence: 97%
“…In line with this, phylogenetic character reconstruction studies suggested multiple origins of betalains from anthocyanin accumulating plants and reversals to anthocyanin production or complete loss of pigmentation trait (Brockington et al, 2011). The possibility of multiple phylogenetic origins of betalain pigmentation trait seems to be partially supported by reports on existence of two enzymes for formation of a betalain compound i.e., involvement of UDP-glucose:betanidin-5-O-glucosyltransferase (B5GT) (Vogt et al, 1999a) and UDP-glucose:cyclo-DOPA-5-O-glucosyltransferase (cD5GT) (Sasaki et al, 2005a,b) in formation of betanin, and diphenol oxidase (DO) activity of TYR or CYP76AD1 in L-DOPA oxidation leading to cyclo-DOPA formation (Steiner et al, 1999;Hatlestad et al, 2012;Suzuki et al, 2014).…”
Section: Mutual Exclusiveness Of Anthocyanins and Betalainsmentioning
confidence: 98%
“…This exclusivity remains unexplained, and is, perhaps, surprising given that gene homologues for a key enzyme in betalain biosynthesis are present in anthocyanic plants (Christinet et al, 2004) and that betanidin 6-O-glucosyltransferase, which catalyses the glucosylation of betacyanin, can also efficiently glucosylate the anthocyanidins (Vogt et al, 1997). There is, moreover, no apparent physiological barrier that prevents the two pigments from co-occurring; a recent study transferred part of the betalain biosynthetic pathway into cell cultures of potato, petals of Antirrhinum and shoots of Arabidopsis, and demonstrated that betalain production was possible in these normally anthocyanic plants when they were fed with a betalain intermediate, L-DOPA (Harris et al, 2012). Indeed, Clement and Mabry (1996) posited that the ancestor of the Caryophyllales could have held both types of pigments, but that one or the other was lost as species evolved.…”
Section: Introductionmentioning
confidence: 96%
“…Catecholamines, such as dopamine, are synthesized from levodopa precursor by tyrosine-hydroxylase and have important roles as neurotransmitters in the central nervous system and in PD, once the dopamine depletion is the responsible for the hallmark symptoms of disease (Missale et al 1998). The presence of cathecolamines such as dopamine has been reported in P. oleracea (Gandía-Herrero et al 2009, Weng et al 2005 as well as the presence of levodopa in P. oleracea and the ability of converting tyrosine to levodopa (Harris et al 2012).…”
Section: Discussionmentioning
confidence: 99%